CRIMINALIZATION AND PROSECUTION OF HUMAN TRAFFICKING IN ETHIOPIA: ASSESSING THE LEGAL FRAMEWORK IN LIGHT OF INTERNATIONAL STANDARDS - Z.Sh. Woldemichael (BRICS Law Journal)
As is the case in many countries, in Ethiopia human trafficking causes multi-dimensional harmful consequences on individuals. With a view to addressing the problem, in 2012 Ethiopia acceded to the Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children, supplementing the United Nations Convention against Transnational Organized Crime. For the purpose of translating the requirements of the UN Trafficking Protocol into reality, the government has taken various steps including legislative measures. Proclamation No. 909/2015 (Prevention and Suppression of Trafficking in Persons and Smuggling of Migrants Proclamation) is the most recent law adopted to deal with smuggling of migrants and human trafficking. The Proclamation comprises four key aspects: criminalization and prosecution; prevention; protection, rehabilitation and compensation; and cooperation. This article critically examines whether the criminalization and prosecution aspect of the Proclamation complies with international standards.